Individual variation in reproductive success in the wandering Albatross - Jones, M Genevieve W (Department of Biological Sciences, 2015)
To conserve threatened species it is important to protect the productive individuals, and so I aimed to identify factors accounting for individual-level variation in long-term reproductive success. I examined current breeding characteristics that might explain past reproductive performance amongst experienced breeders.